THE EFFECT OF FEEDING AND MAIN CUTTING ANGLE ON THE SURFACE ROUGHNESS OF METAL RESULTING FROM FLAT TURNING ON ST 37 STEEL MATERIAL - Mukhnizar , Mukhnizar; Muhammad Akbar Pratama; Risal Abu (Ikatan Dosen Menulis, 2025)
High-quality turning is achieved through optimal cutting conditions. One of the variables affecting cutting conditions is surface roughness. The aim of this research is to examine the influence of feed rate and main cutting angle on the surface roughness of flat turning results on ST 37 steel material. The turning process was carried out with a cutting depth of 0.5 mm during the finishing process by varying the feed rate and main cutting angle. The feed rates used were 0.070 mm/rev, 0.281 mm/rev, and 0.450 mm/rev on ST 37 workpieces with a diameter of 24 mm and a length of 44 mm, which were turned down to a diameter of 23 mm along the same 44 mm length using a High Speed Steel (HSS) cutting tool. After the turning process, the surface roughness of the workpieces was measured using a Mitutoyo SJ-201P Surface Tester. The results of this study show that at main cutting angles of 80° and 90° and feed rates of 0.070 mm/rev, 0.281 mm/rev, and 0.450 mm/rev, the smallest surface roughness value achieved was Ra = 2.88 µm, corresponding to surface roughness grade N7, which occurred at a main cutting angle of 80° and a feed rate of 0.070 mm/rev. Meanwhile, the highest surface roughness value was Ra = 8.85 µm, corresponding to surface roughness grade N9, which occurred at a main cutting angle of 90° and a feed rate of 0.450 mm/rev.